2017
DOI: 10.1021/acs.langmuir.7b03852
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Interfacial Conjugation of Chitosan with Cinnamaldehyde during Homogenization Improves the Formation and Stability of Chitosan-Stabilized Emulsions

Abstract: The emulsifying properties of a natural cationic polysaccharide (chitosan) were improved by in situ conjugation with a natural essential oil (cinnamaldehyde, CA) during homogenization. In the absence of CA, chitosan-coated medium-chain triglyceride droplets were highly susceptible to creaming and coalescence at pH values ranging from 1 to 6.5. However, incorporation of relatively low levels of CA in the oil phase greatly improved the formation and stability of oil-in-water emulsions. These effects were attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Similarly, in situ covalent cross-linking of chitosan with CA during homogenization was used to enhance the emulsifying properties of the chitosan (Chen et al, 2017). The CA molecules can form covalent bonds with chitosan chain to form an amphiphilic conjugate.…”
Section: Formation Of Nanoemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in situ covalent cross-linking of chitosan with CA during homogenization was used to enhance the emulsifying properties of the chitosan (Chen et al, 2017). The CA molecules can form covalent bonds with chitosan chain to form an amphiphilic conjugate.…”
Section: Formation Of Nanoemulsionsmentioning
confidence: 99%
“…Also, the CA molecules can covalently cross-link the chitosan chains at the oil droplet surfaces, causing the creation of a rigid surface that can stabilize NE against coalescence ( Figure 5). Chen et al (2017) addressed three potential advantages of their developed approach: (1) emulsifiers can be formed from all-natural components without the need for synthetic emulsifiers or organic solvents; (2) only a low level of CA is needed, which could be replaced by cinnamon oil; and (3) high stability to droplet coalescence is achievable.…”
Section: Formation Of Nanoemulsionsmentioning
confidence: 99%
“…Addition of whey protein microgels and bacterial cellulose is another solution recently published to impart yield stress to the dispersing phase and overcome the emulsion coalescence [164,165]. The second factor is frequently manipulated by increasing the rigidity or elasticity of the interface to reduce the merging of droplets [166,167]. Polymers such as cellulose esters and poly(N-isopropylacrylamide) have been used for this purpose, the latter being triggerable by temperature changes due to its characteristic LCST phase transition [168,169].…”
Section: Emulsion Stabilizationmentioning
confidence: 99%
“…investigated the creaming and coalescence of the emulsion prepared by modified chitosan at pH value ranging from 1.0 to 6.5, by cinnamaldehyde. They found that the natural essential oil can covalently modify the chitosan, which can raise the efficiency of the emulsifying process and stabilize the o/w emulsion . Dammak and Sobral researched the effect of different biopolymers on the stabilization of o/w emulsion.…”
Section: Introductionmentioning
confidence: 86%